ANALISA BUCK CONVERTER DAN BOOST CONVERTER PADA PERUBAHAN DUTY CYCLE PWM DENGAN MEMBANDINGKAN FREKUENSI PWM 1,7 Khz DAN 3,3 Khz - Hendi Matalata; Leily W Johar (Jurnal Ilmiah Universitas Batanghari Jambi, 2018)
Buck-Boost Converters are electric power supply device for raising and lowering the voltage DC (Direct Current) power supply equipment according to needs of the electrical load, this research is designed to Buck-Boost Converter and Converter on the 12 Volt power supply, the design of a Buck Converter power supply derived 5 Volt, 6Volt and 6 Volt design while the Boost Converter power supply 12 Volt offered up to 16 Volt, 19 Volt and 22 Volts in a way set the duty cycle of PWM frequency settings in 1.7 Khz and 3.3 Khz. Results research indicates the State of the differences in each frequency in the set output voltage ripple shape obtained is different, however, in the design of this research have been successfully carried out as expected.Keywords: buck converter, boost converter, change in duty cycle